Segmentation of the melanoma lesion and its border - Surówka, Grzegorz; Ogorzałek, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
Segmentation of the border of the human pigmented lesions has a direct impact on the diagnosis of malignant melanoma. In this work, we examine performance of (i) morphological segmentation of a pigmented lesion by region growing with the adaptive threshold and density-based DBSCAN clustering algorithm, and (ii) morphological segmentation of the pigmented lesion border by region growing of the lesion and the background skin.
Keywords: computer-aided diagnosis; DBSCAN; melanoma; region growing; segmentation